Downregulation of miRNA-29, -23 and -21 in urine of Duchenne muscular dystrophy patients. (22nd March 2018) - Catapano, Francesco; Domingos, Joana; Perry, Mark; Ricotti, Valeria; Phillips, Lauren; Servais, Laurent; Seferian, Andreea; Groot, Imelda de; Krom, Yvonne D; Niks, Erik H; Verschuuren, Jan JGM; Straub, Volker; et al.
Aim: To study the signature of 87 urinary miRNAs in Duchenne muscular dystrophy (DMD) patients, select the most dysregulated and determine statistically significant differences in their expression between controls, ambulant (A) and nonambulant (NA) DMD patients, and patients on different corticosteroid regimens.Patients/materials & methods: Urine was collected from control (n = 20), A (n = 31) and NA (n = 23) DMD patients. miRNA expression was measured by reverse transcription-quantitative PCR.Results: miR-29c-3p was significantly downregulated in A DMD patients while miR-23b-3p and miR-21-5p were significantly downregulated in NA DMD patients compared with age-matched controls.Conclusion: miR-29c-3p, miR-23b-3p and miR-21-5p are promising novel noninvasive biomarkers for DMD, and miR-29c-3p levels are differentially affected by different steroid regimens, supporting the antifibrotic effect of steroid therapy.